2021
DOI: 10.1097/acm.0000000000004208
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Team Rounding: A Cross-Specialty Inpatient Care Staffing Program to Manage COVID-19 Surges

Abstract: Problem The SARS-CoV-2 (COVID-19) pandemic presented numerous challenges to inpatient care, including overtaxed inpatient medicine services, surges in patient censuses, disrupted patient care and educational activities for trainees, underused providers in certain specialties, and personal protective equipment shortages and new requirements for physical distancing. In March 2020, as the COVID-19 surge began, an interdisciplinary group of administrators, providers, and trainees at Brigham and Women’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The Telehealth technology category had 20 related articles and was the second most utilized intervention. For example, Becker et al concluded in their article that a valuable way to manage COVID-19 surges is virtual rounding [12]. Along a similar line, Hannemann et al found that digital health technologies can provide a platform to expand the offering of healthcare services [13].…”
Section: Resultsmentioning
confidence: 99%
“…The Telehealth technology category had 20 related articles and was the second most utilized intervention. For example, Becker et al concluded in their article that a valuable way to manage COVID-19 surges is virtual rounding [12]. Along a similar line, Hannemann et al found that digital health technologies can provide a platform to expand the offering of healthcare services [13].…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] Strategies included rounding via telephone or video-based conferencing platforms and limiting the number and proximity of rounding team members. 5 Some graduate medical education programs initially restricted trainees from providing direct care to patients with COVID-19, 6 and accreditation bodies recommended temporarily withdrawing students from patient-facing activities. 7 Although well intentioned, these changes may have affected clinical education during rounds.…”
mentioning
confidence: 99%
“…As the coronavirus disease 2019 (COVID-19) pandemic spread across the United States in spring 2020, inpatient IM teams developed virtual and hybrid modifications to traditional inpatient rounding to mitigate potential nosocomial transmission of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) and to conserve personal protective equipment (PPE) 2–4 . Strategies included rounding via telephone or video-based conferencing platforms and limiting the number and proximity of rounding team members 5 . Some graduate medical education programs initially restricted trainees from providing direct care to patients with COVID-19, 6 and accreditation bodies recommended temporarily withdrawing students from patient-facing activities 7…”
mentioning
confidence: 99%
“…They were actively involved in efforts to optimize triaging of patients, turn emerging evidence into guidelines, and create multidisciplinary teams to improve care. [7][8][9][10] With little preparation, trainees brought their strong work ethic, eagerness to learn, and readiness to question norms to improving systems and those who practice within them. By being involved in firsthand, real-time systemic endeavors, residents contributed to academic health systems while learning how to practice independently within them.Author affiliations and article information are listed at the end of this article.…”
mentioning
confidence: 99%
“…When academic health systems faced unprecedented hospital admissions and rapidly shifting treatment paradigms, frontline residents reliably contributed to improvement endeavors. They were actively involved in efforts to optimize triaging of patients, turn emerging evidence into guidelines, and create multidisciplinary teams to improve care . With little preparation, trainees brought their strong work ethic, eagerness to learn, and readiness to question norms to improving systems and those who practice within them.…”
mentioning
confidence: 99%